Ecological Habit Inferences of the Extinct Porcupine Coendou magnus Lund, 1839 (Rodentia, Erethizontidae) from Brazilian Intertropical Region - Dantas, Mário André Trindade; da Costa, João Paulo (Anuário do Instituto de Geociências, 2024)
Through the use of two indices estimated from measurements of the humerus and ulna, we suggested the possible ecological habit of the extinct porcupine Coendou magnus Lund, 1839 from the Late Pleistocene in the Brazilian Intertropical Region. The analyzed specimen was found in Toca da Barriguda cave (Campo Formoso/BA, Brazil), weighed 9 kg, and lived in a low-density forest at 33,171-33,765 cal yr BP. All extant species of the Coendou genus are suspensory, and these indices suggest the same ecological habit for C. magnus.